Harta kekayaan dalam perkawinan: Analisis normatif dan pertimbangan Hakim Nomor 2802/Pdt.G/2018/Dpk - Maulana, Muhammad Achdan (Maliki Interdisciplinary Journal, 2026)
This article aims to explore how the concept of joint property is understood in Islamic law and in the positive legal system in Indonesia. The term joint property, commonly referred to as ‘gono-gini’, refers to all assets acquired by a husband and wife through their joint efforts during their marriage. The existence of this property demonstrates the contribution and cooperation in building the family's economy. However, in practice, disputes often arise that lead to divorce, especially when each party considers most of the property to be their own. Based on this issue, the researcher felt the need to examine the regulation of gono-gini property from the perspective of Islamic law and legislation. The research was conducted using a qualitative approach through literature review, both from books and scientific articles, which were analysed in depth to achieve the objectives of the article. The findings of the study show that the regulation of joint property in Islamic law is contained in Articles 85 to 97 of the KHI, while in positive law it is regulated in Article 35 of Law Number 1 of 1974 concerning Marriage.